STRATEGI PEMASARAN POLITIK CALEG MILENIAL PARTAI NASDEM KABUPATEN KARAWANG PADA PEMILU 2024 - Hanifah Nur Rohmah; Ahmad Mudzaki Elyas; Vierra Pramuliawati; Haura Atthahara (Program Studi Ilmu Pemerintahan FISIP Universitas Galuh, 2025)
Elections are a way to realize the democratic system and practice the fourth precept of Pancasila. The 2024 election highlights the significant role of millennials and Gen Z, who account for 55% of voters. Dian Fahrud Jaman, a millennial candidate from the NasDem Party, managed to win a seat in the Karawang DPRD with an innovative political marketing strategy. This research aims to analyze the political marketing strategy of the Karawang Regency NasDem Party legislative candidate Dian Fahrud Jaman in the 2024 election, using Everett Rogers' Diffusion of Innovations approach which considers aspects of innovation, communication channels, time, and social systems. This research uses a qualitative method with a case study. Data collection techniques through interviews, observation, and documentation and purposive sampling to determine research informants. The results showed that the political marketing strategy applied by Dian Fahrud Jaman of the NasDem Party of Karawang Regency was effective in increasing her electability among young voters and various segments of society. Dian Fahrud Jaman through an innovative approach that includes changing the party's image, using communication channels both interpersonal and social media, good timing, in-depth understanding of social norms and social structures has been successful in gaining voter support. The findings of this study provide insight into the importance of innovation and inclusive political marketing strategies in winning elections in the context of evolving political dynamics.